Vitamin D in youth with Type 1 diabetes: prevalence of insufficiency and association with insulin resistance in the SEARCH Nutrition Ancillary Study. Issue 11 (29th August 2013) - The, N. S.; Crandell, J. L.; Lawrence, J. M.; King, I. B.; Dabelea, D.; Marcovina, S. M.; D'Agostino, R. B.; Norris, J. M.; Pihoker, C.; Mayer‐Davis, E. J.
Abstract Aims To determine the prevalence of plasma vitamin D (25‐dihydroxyvitamin D) insufficiency in individuals with Type 1 diabetes and to determine the cross‐sectional and longitudinal associations of plasma vitamin D with insulin resistance. Methods Participants from the SEARCH for Diabetes in Youth Study [n = 1426; mean age 11.2 years (sd 3.9)] had physician‐diagnosed Type 1 diabetes [diabetes duration mean 10.2 months (sd 6.5)] with data available at baseline and follow‐up (approximately 12 and 24 months after baseline). Insulin resistance was estimated using a validated equation. Cross‐sectional and longitudinal multivariate logistic regression models were used to determine the association of plasma vitamin D with insulin resistance, adjusting for potential confounders. Results Forty‐nine per cent of individuals had plasma vitamin D < 50 nmol/l and 26% were insulin resistant. In cross‐sectional multivariate analyses, participants who had higher plasma vitamin D (65 nmol/l) had lower odds of prevalent insulin resistance than participants with lower plasma vitamin D (25 nmol/l) (odds ratio 0.70, 95% CI 0.57–0.85). This association was attenuated after additional adjustment for BMI z‐score, which could be a confounder or a mediator (odds ratio 0.81, 95% CI 0.64–1.03). In longitudinal multivariate analyses, individuals with higher plasma vitamin D at baseline had lower odds of incident insulin resistance, but this was not significant (odds ratio 0.85, 95% CI 0.63–1.14). Conclusions Vitamin D insufficiency is common in individuals with Type 1 diabetes and may increase risk for insulin resistance. Additional prospective studies are needed to determine the association between plasma vitamin D and insulin resistance, and to further examine the role of adiposity on this association.